Atomoxetine in comorbid ADHD/PTSD: A randomized, placebo controlled, pilot, and feasibility study. Issue 4 (21st March 2022) - Wang, Zhewu; Zuschlag, Zachary D.; Myers, Ursula S.; Hamner, Mark
Abstract: Background: PTSD and ADHD often occur comorbidly. Research indicates that the cognitive deficits in PTSD may be related to the same disturbance of fronto‐temporal systems as observed in ADHD, and ADHD has been shown to impact PTSD treatment outcomes. The presented study evaluated the safety and efficacy of atomoxetine in Veterans with comorbid ADHD/PTSD. Methods: A double blind, randomized, placebo controlled, cross‐over pilot and feasibility study was conducted. Atomoxetine was examined as an adjunctive treatment over this 10 weeks, two phase, crossover study which compared treatment with atomoxetine 80 mg daily to placebo daily. The primary outcome was improvement in ADHD symptoms as measured by the Conners' Adult ADHD Rating Scales‐Self‐Report: Short Version (CAARS‐S:S), the Barkley Adult ADHD Rating Scale‐IV (BAARS‐IV), and the Adult ADHD Quality of Life‐29 (AAQoL‐29). Secondary outcomes included the Clinician Administered PTSD Scale (CAPS), Medical Outcomes Study 36‐Item Short‐Form Health Survey (SF‐36), and the response inhibition task Go/NoGo (GNG). Results: Atomoxetine treated patients had greater reductions in ADHD symptoms as defined by total scores on the CAARS‐S:S ( F (1, 29)  = 6.37, p  = .017); both the BAARS‐IV ( F (1, 26)  = 3.16, p  = .087); and GNG overall errors test ( F (1, 29)  = 3.88, p  = .06), reached a trend level of significance. No significant differences were noted in quality of life assessments, GNG latency periods, or CAPS scores. Atomoxetine was well‐tolerated with no serious adverse events observed. Conclusions: In Veterans with ADHD comorbid with PTSD, atomoxetine demonstrated modest efficacy for ADHD symptoms; quality of life measures and PTSD symptoms were not affected.